COVID-19 Outbreak and Surgical Practice: Unexpected Fatality in Perioperative Period - Aminian, Ali (Ann Surg, 2020)
Little is known about surgical practice in the initial phase of coronavirus disease 2019 (COVID-19) global crisis. This is a retrospective case series of 4 surgical patients (cholecystectomy, hernia repair, gastric bypass, and hysterectomy) who developed perioperative complications in the first few weeks of COVID-19 outbreak in Tehran, Iran in the month of February 2020. COVID-19 can complicate the perioperative course with diagnostic challenge and a high potential fatality rate. In locations with widespread infections and limited resources, the risk of elective surgical procedures for index patient and community may outweigh the benefit.